Reflection of Alienation of Human Relations in Morality - Kapačiauskienė, Danutė (Problemos, 1974)
The question is raised in the article as to the appropriateness of the application of the concept of estrangement in the definition of morality. To answer the question one must analyse the way alienation of work affects morality. The effects are the following: 1) moral norms are singled out as special ones from the totality of primitive customs, and moral evaluation loses connection with the economic, political, etc. expediency of human actions; 2) moral principles are considered to be primary with respect to social practice; 3) man is treated as the object, not the subject, of moral upbringing.